Real-Time Imaging of Leaf Apoplastic pH Dynamics in Response to NaCl Stress - Geilfus, Christoph-Martin; Muehling, Karl H. (Frontiers in Plant Science, 2011)
Knowledge concerning apoplastic ion concentrations is important for the understanding of many processes in plant physiology. Ion-sensitive fluorescent probes in combination with quantitative imaging techniques offer opportunities to localise, visualise and quantify apoplastic ion dynamics in situ. The application of this technique to the leaf apoplast is complicated because of problems associated with dye loading. We demonstrate a more sophisticated dye loading procedure that enables the mapping of spatial apoplastic ion gradients over a period of 3 hours. The new technique has been used for the real-time monitoring of pH dynamics within the leaf apoplast in response to NaCl stress encountered by the roots.